2008
DOI: 10.1134/s1995078008090048
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy characterization of ultrasound-sensitive nanocomposite microcapsules

Abstract: In recent years, considerable effort has been devoted to the development and investigation of systems for controlled delivery of drugs. Targeted delivery of drugs significantly increases their efficacy and allows the total drug concentration in the organism to be considerably decreased. In order to solve this task, special containers/carriers have been designed possessing preset and controlled physicochemical and mechanical properties. The function of such containers can be performed, for example, by polymeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…[31] This change of mechanical properties explains the decrease of their sensitivity to ultrasound with increasing volume fraction of Fe 3 O 4 nanoparticles. [29] In summary, the results presented in our work are significantly different from all data described earlier. We showed that the incorporation of ZnO nanoparticles in the capsule shell and change of the volume fraction of ZnO leads to the decrease in Young's modulus and shell elasticity with following fragility increase.…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…[31] This change of mechanical properties explains the decrease of their sensitivity to ultrasound with increasing volume fraction of Fe 3 O 4 nanoparticles. [29] In summary, the results presented in our work are significantly different from all data described earlier. We showed that the incorporation of ZnO nanoparticles in the capsule shell and change of the volume fraction of ZnO leads to the decrease in Young's modulus and shell elasticity with following fragility increase.…”
Section: Resultscontrasting
confidence: 56%
“…However, in recent years only few works were devoted to the investigation of the ultrasonic effect on the properties of nanocomposite microcapsules. [27][28][29] It was established that the integrity and permeability of the shells depend on the duration and power of ultrasonic treatment [27,28] and on the shell thickness and composition. [27,29] But the power used in all known works considerably exceeded the safety levels in ultrasound therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ZnO inhibits the growth of bacteria, primarily Gram-positive. In contrast, the silver nanoparticles are more active against Gramnegative bacteria [23].…”
Section: Fig 2 Influence Of Metal Oxide Nanoparticles At Different mentioning
confidence: 96%